Capillary Hemangioma of the Sphenoid Sinus - Manica, Denise; Piltcher, Otávio Bejzman; Sekine, Leo (Clinical and Biomedical Research, 2011)
Hemangiomas of upper respiratory tract are uncommonly seen in clinical practice, and there are only a few reports of cases arising in the nasal sinuses. Specifically concerning capillary hemangiomas of the sphenoid sinus, as far as we know, there is only one case reported in the literature. This case report describes also a capillary hemangioma of the sphenoid sinus. A 26 year- old man complained of an intense headache and a retronasal bloody drainage. After some days in conservative treatment without any improvement, and after having an imaging study showing partial opacification of the sphenoid sinus, he underwent a left sphenoidectomy. The lesion identified in the region was ressected and sent to histopathological analysis, which revealed a capillary hemangioma. The patient is on follow-up for 12 months now and still asymptomatic. This case report emphasizes the importance of also considering this diagnosis when evaluating paranasal sinuses related complaints, even when faced with a clinical history and ancillary exams indicative of a common inflammatory disease. Despite the good result seen with the surgical management of this patient, this alternative should be carefully chosen, taking into account possible hemorrhagic complications of different hemangiomas